3D Bioprinting Potential Technology for Drug Delivery - Jayanthi, Lakshmi Sampada; Chinthaginjala, Haranath; Tadipatri, Sameer; Thippeswamy Gari, Suryaprathap; Goud Gadwala Vajagouni, Nishanth (Indian Journal of Pharmaceutical Education and Research, 2026)
ABSTRACT The advent of three-Dimensional (3D) bioprinting offers transformative opportunities in tissue engineering, enabling the precise fabrication of functional tissues and organs for medical and research applications. This study aims to explore the scientific advancements in 3D bioprinting techniques and bioinks while evaluating their potential to overcome current biomedical challenges. Using a comprehensive review of cutting-edge bioprinting methods, this work analyses the integration of diverse bioink formulations, printing strategies, and their applications in areas such as regenerative medicine and drug testing. The findings reveal significant progress in creating complex tissue structures and organ models, although limitations such as vascularization, regulatory hurdles, and ethical concerns persist. Conclusively, addressing these barriers is critical to realizing the full potential of bioprinting, paving the way for innovative solutions in organ transplantation, personalized medicine, and disease modelling.
Keywords: 3D bioprinting; Regenerative medicine; Personalized medicine; Bioinks.